Protein Profile of Granulosa Cells in Cyclic and Acyclic Buffaloes - S. Satheshkumar; B. Revathipriya; S. Sakthivel; K. Brindha; M. Parthiban (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The objective of the study is to analyze the alterations in the protein profile of follicular cells in normal cyclic and acyclic anoestrus water buffaloes. Ovaries from sexually mature buffaloes were collected from abattoir and categorized into two groups viz., i. Cyclic and ii. Acyclic. In both the categories of ovaries, the follicular fluid (FF) was aspirated from all large follicles (> 9mm diameter) and small follicles (< 9 mm diameter) separately. FF was centrifuged and four categories of pelleted granulosa cells (CSG and ASG: Granulosa cells of small follicles in cyclic and acyclic groups respectively; CLG and ALG: Granulosa cells of large follicles in cyclic and acyclic groups respectively) were subjected for SDS-PAGE analysis. A total of 30 and 18 bands (from 7.1 to 209.0 kDa) were observed in CSG and CLG categories, while 16 bands in each of the ASG and ALG were recorded. It was observed that 40 per cent of bands present in the CSG group were not observed in CLG group. On the contrary, almost all the proteins found in ASG group were retained in the ALG group. It can be inferred that a group of small molecular weight granulosa cell proteins, correlating to IGF / IGFBP system, play a key role in providing a favorable proteo-genomic environment in the early stages of follicular development. In acyclic animals, retaining of such proteins in the large follicles indicated that the non-availability of metabolic factors needed for final maturation of follicles.